Organizational culture in Japanese companies in the Czech Republic - Mošová, Valentýna; Martínez Pantoja, Yadira Ixchel; Chvátalová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis examines how Japanese companies operating in the Czech environment function within a different cultural and organizational environment. It investigates whether traditional Japanese workplaces practices are preserved, adapted to the Czech context or hybrid approaches are developed focusing in the areas of leadership styles, communication, career advancement opportunities and diversity, equity and inclusion. This thesis is divided into a theoretical section, which covers Hofstede and Trompenaars' cultural frameworks and key aspects of Japanese organizational culture, and an empirical section based on a qualitative research approach with subsequent analysis of the findings, which are compared to the theoretical frameworks, allowing for greater understanding of the subject.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses